Molecular Characterization and Phylogenetic Relationships of Melon (Cucumis melo L. Meloni Cultivar) Based on Expression of Andromonoecious Gene - Eka Wasi’ Al-Mughni; Budi Setiadi Daryono (HAYATI Journal of Biosciences, 2020)
Melon (Cucumis melo L.) is one of horticultural commodities with good economic prospect for melon farmers because of several advantages. 'Meloni' is result of crossing between ‘Sun Lady-3’ and ‘PI 371795’ by Genetics and Breeding Laboratory, Faculty of Biology, UGM. The 'Meloni' plant produces females flowers that expressed by CmACS-7 gene and it can be expected that melon plants 'Meloni' included in the primitive cultivars, while 'Meloni' is a cultivation cultivar. The aim of this research is to study the relation of 'Meloni' kinship to primitive and modern cultivars. Characterization of the CmACS-7 gene is begun by a total isolation process of RNA from a sample of melon plant flowers and detection using a specific primer. The cDNA bands obtained are sequenced and then phylogenetic analysis is performed based on CmACS-7 gene expression using MEGA 7.0. Result of this study show that the presence of the CmACS-7 gene in female and hermaphrodite flowers of ‘Meloni’, ‘PI 371795’, ‘Sun Lady-3’, and ‘Hikapel’. Phylogenetic tree analyze show that ‘Meloni’ from female plant, ‘PI 371795’ and ‘Sun Lady-3’ have closely relation, while 'Hikapel' separated from other cultivars.